Recent researches of the bio-inspired nano-carbon reinforced metal matrix composites. (April 2020) - Shu, Rui; Jiang, Xiaosong; Sun, Hongliang; Shao, Zhenyi; Song, Tingfeng; Luo, Zhiping
Abstract: Natural materials usually have excellent performance for their special structures. Learning from the nature may catalyze the creation of artificial composites with unprecedented performance and functionalities. To realize this bio-inspired design idea on nano-carbon reinforced metal matrix composites, it is indispensable to understand and quantify the design principles of natural materials and consider the inherent characteristics of artificial materials and conditions of engineering applications. In this paper, recent researches of the bio-inspired nano-carbon reinforced metal matrix composites are reviewed to highlight the scientific and technological questions to obtain the bio-inspired structure artificial composites. These include the fabrication methods for solving the dispersion problem of nano-carbon and achieving the bio-inspired structure, characterization of microstructure and properties of bio-inspired composites. The interface and reinforcement mechanisms are emphatically investigated and discussed, in this way to help unveil natural design principles and provide reference for the future research of bio-inspired composites.